"Justification by Faith": Richard Baxter's Influence upon John Wesley - Cunningham, Joseph William (The Asbury journal, 2009)
The original article was published with the wrong author, Floyd T. Cunningham. Joseph W. Cunningham is the correct author. The Journal and Article has been modified to reflect the correct author.